2007
DOI: 10.1152/ajpheart.01236.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-restricted restoration of nitric oxide synthase 3 attenuates left ventricular remodeling after chronic pressure overload

Abstract: Although nitric oxide synthase (NOS)3 is implicated as an important modulator of left ventricular (LV) remodeling, its role in the cardiac response to chronic pressure overload is controversial. We examined whether selective restoration of NOS3 to the hearts of NOS3-deficient mice would modulate the LV remodeling response to transverse aortic constriction (TAC). LV structure and function were compared at baseline and after TAC in NOS3-deficient (NOS3(-/-)) mice and NOS3(-/-) mice carrying a transgene directing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 27 publications
2
40
1
2
Order By: Relevance
“…This deviates from previous reports where cardiac myocyte-specific restoration of eNOS expression in NOS3 −/− mice did not attenuate fibrosis in response to TAC 39 and mice with a cardiac myocytespecific eNOS transgene also exhibited unchanged fibrosis in the remote myocardium after MI. 34 This suggests that the systemic NOS inhibition with L-NAME in our experiments abrogated the modulation of profibrotic cytokines by NOS in neighboring cells (eg, endothelial cells) rather than in cardiac myocytes.…”
contrasting
confidence: 99%
“…This deviates from previous reports where cardiac myocyte-specific restoration of eNOS expression in NOS3 −/− mice did not attenuate fibrosis in response to TAC 39 and mice with a cardiac myocytespecific eNOS transgene also exhibited unchanged fibrosis in the remote myocardium after MI. 34 This suggests that the systemic NOS inhibition with L-NAME in our experiments abrogated the modulation of profibrotic cytokines by NOS in neighboring cells (eg, endothelial cells) rather than in cardiac myocytes.…”
contrasting
confidence: 99%
“…A study found that, after chronic pressure overload, NOS3 Ϫ/Ϫ mice had increased hypertrophy, fibrosis, and contractile dysfunction compared with WT mice (41). In addition, mice with cardiac myocyte-specific NOS3 overexpression had limited hypertrophy and contractile dysfunction after pressure overload and myocardial infarction (10,23). Furthermore, it is known that I Ca plays a role in hypertrophy (14).…”
Section: Nos3 and Arrhythmogenesismentioning
confidence: 99%
“…Abundant evidence suggests that nitric oxide (NO) has critical roles in the regulation of myocardial function and structure (5,24,48) and blood pressure (23,50). NO plays a pivotal role in cytokine-induced myocardial dysfunction (17,30,52), either attenuating or exacerbating the adverse hemodynamic sequelae associated with systemic inflammation.…”
mentioning
confidence: 99%